Empyema Necessitans Complicating Pleural Effusion Associated with Proteus Species Infection: A Diagnostic Dilemma - M. S. Yauba; H. Ahmed; I. A. Imoudu; M. O. Yusuf; H. U. Makarfi (Case Reports in Pediatrics)
Background. Empyema necessitans, a rare complication of pleural effusion, could result in significant morbidity and mortality in children. It is characterized by the dissection of pus through the soft tissues and the skin of the chest wall. Mycobacterium tuberculosis and Actinomyces israelii are common causes but Gram negative bacilli could be a rare cause. However, there were challenges in differentiating between Mycobacterium tuberculosis and nontuberculous empyema in a resource poor setting like ours. We report a child with pleural effusion and empyema necessitans secondary to Proteus spp. infection. Methods. We describe a 12-year-old child with empyema necessitans complicating pleural effusion and highlight management challenges. Results. This case was treated with quinolones, antituberculous drugs, chest tube drainage, and nutritional rehabilitation. Conclusion. Empyema necessitatis is a rare condition that can be caused by Gram negative bacterial pathogens like Proteus species.